Peran Lembaga Keuangan Mikro Syariah Pondok Pesantren dalam Meningkatkan Ekonomi Umat di Indonesia - Jannah, Miftakhul; Kusbiantoro, Sigit; Hannan, Fais Faizul (Al-Amien Prenduan for Islamic Institute, 2024)
The dynamics of Islamic boarding schools in Indonesia have experienced rapid development. Now, Islamic boarding schools are not only synonymous with religious educational institutions, but they are also expected to contribute to the economic life of the people. The aim of this research is to analyze the role of Islamic boarding schools in efforts to empower the people's economy. This research is a literature study that uses a qualitative descriptive approach. This research found that Islamic boarding schools have sufficient resources and capital to serve as a basis for economic empowerment of the community. With these resources and capital, Islamic boarding schools can carry out various activities oriented towards the economic empowerment of local people. This research uses qualitative research with a library approach. The results of this research are that in practice the community empowerment program carried out by Islamic boarding schools still uses the old system, namely not the digital system which is currently being developed in society, but what is carried out by Islamic boarding schools can be in direct contact with the community so that it remains in accordance with vision and mission of an Islamic boarding school that upholds the principle of mutual help.